Unravelling the interplay between Harmattan wind and baroreflex functions: implications on environmental health and cardiovascular pathophysiology - Mayowa Jeremiah Adeniyi; Oyesanmi A. Fabunmi; Ayoola Awosika (Open Exploration Publishing Inc., 2024)
Harmattan is a season characterized by dust, cold, and sub-humid trade winds in Sub-Saharan countries. It's similar to meteorological phenomena like Asian dust storms, Santa Ana winds, Australian bushfires, and Saharan dust in the Caribbean. It causes profound changes in the cardiorespiratory system in apparently healthy individuals and increases the risk of hospitalization in susceptible individuals. Exposure to these extreme conditions has been associated with alterations in autonomic function and baroreceptor sensitivity thus resulting in dysregulation of blood pressure control mechanisms. Baroreceptors are critical regulators of hemodynamics and cardiovascular function. They play a vital role in the short-term responses to blood pressure perturbation and are essential for acute restoration of blood pressure following cold exposure. Harmattan wind contains a barrage of chemicals, dust, and particulate matters depending on industrialization, natural and human activities. Particulate matter from Harmattan dust can trigger systemic inflammation and oxidative stress, exacerbating endothelial dysfunction and impairing vascular reactivity thus contributing to the pathogenesis of alterations in baroreceptor insensitivity, and cardiovascular diseases, including hypertension and atherosclerosis. Furthermore, fine particulate matter from dust may penetrate deep into the respiratory tract, activating pulmonary sensory receptors and eliciting reflex responses that influence autonomic tone. The presence of rich acrolein smokes and non-essential heavy metals such as cadmium, lead, and mercury in Harmattan wind also reduces baroreflex sensitivity, culminating in a sustained increase in diastolic and systolic blood pressure. This integrated review aims to provide valuable insights into how changes in each of these environmental constituents alter vital pathophysiologic and immunologic mechanisms of the body leading to baroreceptor instability and ultimately hemodynamic imbalance using available primary studies. Understanding this intricate interplay is crucial for implementing targeted interventions and informed public health strategies to mitigate the adverse effects of extreme environmental exposure and ultimately reduce poor health outcomes in the affected regions.